An event-controlled online trajectory generator based on the human-robot interaction force processing. Issue 1 (14th January 2014) - Jlassi, Sarra; Tliba, Sami; Chitour, Yacine
Abstract : Purpose: – The problem of robotic co-manipulation is often addressed using impedance control based methods where the authors seek to establish a mathematical relation between the velocity of the human-robot interaction point and the force applied by the human operator (HO) at this point. This paper aims to address the problem of co-manipulation for handling tasks seen as a constrained optimal control problem. Design/methodology/approach: – The proposed point of view relies on the implementation of a specific online trajectory generator (OTG) associated with a kinematic feedback loop. This OTG is designed so as to translate the HO intentions to ideal trajectories that the robot must follow. It works as an automaton with two states of motion whose transitions are controlled by comparing the magnitude of the force to an adjustable threshold, in order to enable the operator to keep authority over the robot's states of motion. Findings: – To ensure the smoothness of the interaction, the authors propose to generate a velocity profile collinear to the force applied at the interaction point. The feedback control loop is then used to satisfy the requirements of stability and of trajectory tracking to guarantee assistance and operator security. The overall strategy is applied to the penducobot problem. Originality/value: – The approach stands out for the nature of the problem to be tackled (heavy load handling tasks) and for its vision on the co-manipulation. It is based on the implementation of two main ingredients. The first one lies in the online generation of an appropriate trajectory of the interaction point located at the end-effector and describing the HO intention. The other consists in the design of a control structure allowing a good tracking of the generated trajectory.